Relations of Islam and Indigenous Religion in the Perspective of Living the Qur'an of the Savu Tribes - Mustolehudin; Nur Laili Noviani; Muhammad Dachlan; Joseph Lamont; Harapandi Dahri; Israpil (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2025)
The relationship between Islam and ancestral religion in the Savu tribe in NTT presents an interesting dynamic to study. Islam, which came later in the 19th century, was able to adapt to the culture of the Savu tribe. This study aims to explore and analyze the relationship between Islam and the ancestral religion of the Savu tribe from the perspective of living Qur'an. This research is a qualitative descriptive study based on field research. Data in this study were obtained through interviews, observations, and literature studies. The results of study indicate that the development of Islam in Savu occurred through marriages between native residents and newcomers from Bugis, Kalimantan, and Java. The newcomers, some of whom were traders in Savu Raijua, spread Islam through economic channels. On this island, there is only one mosque that is the center of Islamic worship and education. The practice of living Qur'an occuring between the Muslim community and the Jingitiu community is through socio-religious activities centered in the Jami An-Nur mosque. For example, during the construction of the mosque, the ancestral religious community transported stones and sand. Similarly, during the Eid al-Adha celebration from year to year, non-Muslim residents of the Savu tribe help Muslims to separate the skin of the sacrificial animal, cut it into meat, and distribute it to residents in the area. This study provides invaluable insight into how the living Qur'an can be used to create social harmony between Islam and ancestral beliefs in a pluralistic and multicultural society such as the Savu tribe. The successful integration of Islamic values into local culture depends on an approach based on tolerance, harmony, and respect for local traditions.